PEMIKIRAN KI BAGOES HADIKOESOEMO MENGENAI KONSEP NEGARA - Wildan Nurul Fajar (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2018)
This research aims to describe, analyze, and formulate Ki BagoesHadikoesoemo's political thinking about the State of Indonesia. This study usesa critical character study method which is one of the types of qualitative research.Data collection and information techniques used include study documentationand interviews. The results of the study showed that Ki Bagoes Hadikoesoemohad an important role in the formulation of the basic state of Indonesia in theJakarta Charter. Ki Bagoes Hadikoesoemo had an important role in the first SilaPancasila change as it is now. In Muhammadiyah, Ki Bagoes Hadikoesoemo hasput Baldatun Thayyibatun Wa Rabbun Ghafur as the foundation ofMuhammadiyah's ideals in developing the country as stated in the articles ofassociation Muhammadiyah's.Keywords: Political Thought, Ki Bagoes Hadikoesoemo, State Concept,Muhammadiyah